GIS e Beni Culturali: beni tangibili e beni intangibili - Gattuso, Caterina; Gattuso, Philomène; Pizzi, Atanasio; Roviello, Valentina (Archeomatica, 2019)
Information and intangible data cannot be easily transferred to georeferenced maps; it follows the need to identify elements on the territory based on appropriate correlations. The paper examines two types of heritage, one of a tangible type and one of an intangible one, which have a common strong reference represented by the territory in which they are located. The first consists of the archaeological sites of the colony of Vulturnum, present in the river system of the low plain of the Volturno river in Campania; the second concerns the culture "Arbà«reshà«" which finds its connections in the typological-constructive language and in the peculiar urban conformation of the Albanian-speaking centers.